Les Clubs D’environnement Dans Les Établissements Scolaires Au Maroc: Une Voie Prometteuse Pour L’ancrage De L’éducation À L’environnement - Cherai, Bouamama; El Hnot, Hasnae; Idrissi, Bouhsine El Fellah; Akkaoui, El Ghazi (European Scientific Journal, ESJ, 2017)
This article aims to diagnose the factors of activing and creating environment clubs as unavoidable educational structures helping to anchor environmental education in the Moroccan schools. In order to achieve this objective, questionnaires were distributed to 40 teachers practicing in fifteen schools distributed in three provincial directorates belonging to the regional academy of education and training of Tanger – Tetouan – Al Hoceima. According to the qualitative and quantitative analysis of the results of these questionnaires, environmental clubs constitute important educational structures able to ensure the development of the environmental culture in the educational practices within schools. However, many constraints to the activation of these clubs were reported by the interviewed teachers, in particular those related to the hourly load and the overload of the school curricula, the lack of supervision and the training of teachers and the absence of the teaching and learning materials necessary for environmental education activities. The key element of activating the environmental clubs in schools appears to be initial and continuous training of teachers. This training should focus on the techniques of the integration of the environmental dimension which includes educational projects and innovative activities with attractive scientific, ethical and civic purposes involving all actors and partners.